Validation of the Cutaneous Lupus Erythematosus Disease Area and Severity Index and pSkindex27 for use in childhood-onset systemic lupus erythematosus. Issue 1 (17th November 2018) - AlE'ed, Ashwaq; Aydin, Pinar Ozge Avar; Al Mutairi, Nora; AlSaleem, Alhanouf; Sonmez, Hafize Emine; Henrickson, Michael; Huggins, Jennifer L; Ozen, Seza; Al-Mayouf, Sulaiman M; Brunner, Hermine I
Abstract : Objective: To determine the measurement properties of the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) and the paediatric adaptation of the Skindex29 (pSkindex27) when used in childhood-onset SLE (cSLE). Methods: Patients with mucocutaneous involvement of cSLE were evaluated at the study entry and 6 months later. Besides the CLASI and pSkindex27, the Pediatric Quality of Life Inventory Generic Core scale (PedsQL-GC), its Rheumatology Module (PedsQL-RM), the SLE Disease Activity Index (SLEDAI) and the SLE Damage Index (SDI) were completed. Results: The CLASI and pSkindex27 had high internal consistency (both Cronbach α > 0.82). Children were able to complete the pSkindex27, with self-report and caregiver proxy-reports showing excellent agreement (intraclass correlation coefficient=0.97). The CLASI Activity Score (CLASI-A) was strongly correlated with the mucocutaneous domain score of the SLEDAI as was the CLASI Damage Score (CLASI-D) with that of the SDI (both: Spearman correlation coefficients (rs ) >0.68). pSkindex27 summary scores were moderately correlated with those of the PedsQL-GC and PedsQL-RM (all: rs > |0.51|), the CLASI-A and CLASI-D (both: rs > 0.64), respectively. Patients who experienced a >50% improvement of the CLASI-A between study visits had significantly higher PedsQL-GC and pSkindex27 scores than those without improvement of mucocutaneous features. Conclusion: Both CLASI and pSkindex27 are useful assessment tools in cSLE, active and chronic mucocutaneous lesions and their changes over time can be measured using the CLASI and the pSkindex27 can capture the impact of mucocutaneous involvement on patient health-related quality of life.